2002
DOI: 10.1161/hq0102.101843
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Endothelial Nitric Oxide in Sphingosine-1-Phosphate–Induced Angiogenesis

Abstract: Abstract-Nitric oxide (NO) has been implicated as a critical signaling molecule of angiogenesis. Recently, sphingosine-1-phosphate (S1P) has emerged as a mediator of angiogenesis, and S1P-induced NO synthesis in endothelial cells (ECs) has been reported. To analyze the signaling pathways involved in S1P-induced angiogenesis and clarify the role of NO in this process, we performed in vivo and in vitro angiogenesis assays. S1P activated the phosphatidylinositol-3-kinase (PI3K)/Akt/endothelial NO synthase (eNOS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(93 citation statements)
references
References 33 publications
3
88
0
2
Order By: Relevance
“…[23][24][25] In sparsely plated nonsilencing control siRNA-, Rap1 siRNA-and afadin siRNA-transfected HUVECs, VEGF and S1P increased the phosphorylation of Akt and eNOS. This increase was inhibited in Rap1-or afadin-knockdown HUVECs when compared with control cells ( Figure 5).…”
Section: Regulation Of Proangiogenic Signaling By Afadinmentioning
confidence: 99%
“…[23][24][25] In sparsely plated nonsilencing control siRNA-, Rap1 siRNA-and afadin siRNA-transfected HUVECs, VEGF and S1P increased the phosphorylation of Akt and eNOS. This increase was inhibited in Rap1-or afadin-knockdown HUVECs when compared with control cells ( Figure 5).…”
Section: Regulation Of Proangiogenic Signaling By Afadinmentioning
confidence: 99%
“…Briefly, 0.1 ml growth factor reduced Matrigel (Becton Dickinson, San Jose, CA, USA) was added per well of a 96-well plate, and then MBECs (2  10 4 cells) were added and incubated in (1) regular cell-culture medium (Dulbecco's modified Eagle's medium) for control, (2) MSC condition media alone, (3) astrocyte condition media alone, (4) MSCs coculture with astrocytes conditioned media, (5) MSCs coculture with MBECs conditioned media, (6) MSC condition media with neutralized Ang1 antibody (1 mg/mL, rabbit anti-Ang1 affinity-purified polycolonal antibody, Chemicon, Temecula, CA, USA), and (7) MSC conditioned media with neutralized Flk1 antibody (DC101, 1 mg/mL) for 24 h. All assays were performed in n = 6/group. For quantitative measurements of capillary tube formation, Matrigel wells were digitized under a  4 objective (Olympus BX40) for measurement of total tube length of capillary tube formation using a video camera (Sony DXC-970MD) interfaced with the MCID image analysis system (Imaging Research, St Catharines, Canada) at 5 and 24 h. Tracks of endothelial cells organized into networks of cellular cords (tubes) were counted and averaged in randomly selected three microscopic fields (Rikitake et al, 2002).…”
Section: Western Blotmentioning
confidence: 99%
“…Regulation of eNOS Ser-1177 Phosphorylation and NO Production by AMPK-The production of endothelial NO is important for vascular homeostasis and angiogenesis (42)(43)(44)(45)(46). VEGF stimulation promotes Akt signaling which, in turn, produces NO through the activating phosphorylation of eNOS at residue 1177 (27).…”
Section: Ampk Activation By Hypoxia In Endothelial Cells-to Testmentioning
confidence: 99%
“…Endothelium-derived NO is a positive modulator of angiogenesis (42)(43)(44)(45)(46), although the mechanism by which NO exerts this effect is unknown. In the study reported here, dominant-negative AMPK diminished eNOS phosphorylation on Ser-1177 and NO output under conditions of low oxygen tension, whereas AMPK-inhibition had little if any effect on these parameters in normoxic cultures.…”
Section: Ampk Regulates Capillary Formation In Matrigel Plugs In Vivo-mentioning
confidence: 99%